Allele-specific silencing by RNAi of R92Q and R173W mutations in cardiac troponin T. Issue 10 (May 2022) - Migliore, Loredana; Galvagni, Federico; Pierantozzi, Enrico; Sorrentino, Vincenzo; Rossi, Daniela
Autosomal dominant mutations in sarcomere proteins such as the cardiac troponin T ( TNNT2 ) are the main genetic causes of human hypertrophic cardiomyopathy and dilated cardiomyopathy. Allele-specific silencing by RNA interference (ASP-RNAi) holds promise as a therapeutic strategy for downregulating a single mutant allele with minimal suppression of the corresponding wild-type allele. Here, we propose ASP-RNAi as a possible strategy to specifically knockdown mutant alleles coding for R92Q and R173W mutant TNNT2 proteins, identified in hypertrophic and dilated cardiomyopathy, respectively. Different siRNAs were designed and validated by luciferase reporter assay and following analysis in HEK293T cells expressing either the wild-type or mutant TNNT2 alleles. This study is the first exploration of ASP-RNAi on TNNT2 -R173W and TNNT2 -R92Q mutations in vitro and gives a base for further application of allele silencing as a therapeutic treatment for TNNT2 -mutation-associated cardiomyopathies.